If it's not what You are looking for type in the equation solver your own equation and let us solve it.
12-(-y-19)=12
We simplify the equation to the form, which is simple to understand
12-(-y-19)=12
Remove unnecessary parentheses
12+1y+19=12
We move all terms containing y to the left and all other terms to the right.
+1y=+12-12-19
We simplify left and right side of the equation.
+1y=-19
We divide both sides of the equation by 1 to get y.
y=-19
| 5z^2-4z^4-4=0 | | x=(5x-6)+21 | | 23X-5X^2=-24 | | 4.6=5.8-p | | -(-3-7g)-11=-9-5g | | 6x^2-73x-63=0 | | 3[x-3]+2=13-x | | 3a+7(5a+7b)-10(3+5b)=14ab+50(3+4) | | 2[3x+2(x-2)]+19=(3x+1)*2 | | 8x+3-(7+9x)=-8 | | 2(3c+2d)-2(5c-3d)= | | -(3y-1)-3y+7=2 | | 2x^3-11x^2-x+5=0 | | 3(x+2)=5(3x-2) | | y=x^4-2x^3-3x^2 | | y=80x-5x^2+2 | | 24x+x^2=-1 | | ln(x/(x-9)) | | 3x+ky=25 | | (2x+4)2=25 | | (8x-5)+1=9(x+5) | | 31x^2+5=0 | | x+-7=-6 | | [8x-5]+1=9[x+5] | | ae-yd=y*y | | (-3x-6)(x-1)=0 | | a+0+y+d+e=d(0) | | -5x(5x-5)= | | x+(-7)=-15 | | 5(x-3)-2(x+4)=(x-3)+4(x-1) | | a^4-a^2+5=0 | | 3(x+8)=38-4x |